The Dimensions of Environmental Accounting Philosophy in Higher Education Institutions' Risk Management - Ika Pratiwi, Amelia; Widhianningrum, Purweni; Nurbatin, Defia; Endang Purwati, Ninik (Accounting Department,, 2024)
Purpose — This paper describes how environmental accounting philosophy affects several aspects of risk management in higher education institutions. Design/methodology/approach — This paper employs a qualitative research design with a literature review approach. Findings — The Risk Management framework in higher education institutions is constructed based on philosophical ideals from the environmental accounting dimension. The environmental accounting dimension's philosophical values include profit, people, planet, phenotechnology, and prophet. Based on these five factors, leaders of organizations will always make decisions about their vision and mission, goals, strategies, policies, risk management procedures, and risk classification. Practical implications—The research's results could assist all workers and work unit leaders in understanding how opportunities, hazards, and risk management affect gaining a competitive edge and carrying out the mission and vision of higher education institutions. Originality/value — This paper provides a framework integrating risk management practices in higher education institutions with the five environmental accounting dimensions (profit, people, planet, phenotechnology, and prophet). Keywords — Environmental Accounting, Risk Management, Higher Education. Paper type — Qualitative study